An Investigation On Light Structure Modal Parameter By Using Experimental Modal Analysis Method Via Piezofilm Sensor - Ramli, Mohd Irman; Nuawi, Mohd. Zaki; Abdullah, Shahrum; Mohammad Rasani, Mohammad Rasidi; Ahmad, Muhamad Arif Fadli; Kho, Ko Seng (Penerbit UTM Press, 2017)
This study is conducted to determine the modal parameters namely natural frequencies and mode shapes of aluminum 6061 (Al6061). The parameters are done by conducting a free dynamic vibration analysis. Modal analysis study was conducted by both simulation and experimental approaches. The simulation was conducted via ANSYS software while the experimental work was performed through impact hammer testing to determine the vibration parameter. Two sensors i.e. piezoelectric film and accelerometer were used. The result obtained were ya = 302.02x – 52.51 (accelerometer) and yp = 295.78x - 41.73 (piezofilm). ya (accelerometer) and yp (piezofilm) is linear equation of the data plotted according to the reading from mode shape versus natural frequency. The relation between natural frequency from accelerometer and piezofilm for the rectangular-shaped specimen was ya = 1.02yp – 9.90 and can be concluded that the regression ratio of 1.02 was approximately 1.0 which agreed with the status of piezoelectric film sensor that can be used as an alternative sensor for accelerometer. There was a good results agreement between simulation and experimental work outcome.